Pictograph system for diagnosis making and data management in endodontics - Abu Hasna, Amjad; Pinto, Alana Barbosa Alves; Minhoto, Giovanna Bignoto; Corazza, Bruna Jordão Motta; Carvalho, Cláudio Antonio Talge; Ferrari, Carlos Henrique (Brazilian Dental Science, 2020)
ABSTRACT Objective: this questionnaire aimed to evaluate the approval of a new pictograph system for endodontic diagnosis by undergraduate and graduate students/endodontist instead of a conventional method. Methods: after a presentation to a total of 224 participants explaining the pictograph system, the participants (166 undergraduate students and 58 graduate students/endodontist) received a standardized questionnaire with three questions. The data were analyzed using the multprop macro basing on Tukey’s test for multiple comparison with (P ? 0.05). The first question was to define the education level of the participants; the second question about which diagnosis method is preferred; and the third question about the intention of using one of the methods in the future. The questionnaire was realized in May 2019. The response rate was 97.7%. Results: the first question showed that 74.10% and 25.90% were undergraduate and graduate students/endodontist respectively. After statistical analysis there was no significant difference between the groups in the second and the third questions. In the second question (71.08% and 62.06%) of undergraduate and graduate student/endodontists respectively preferred the pictograph method over the conventional method. In the third question (60.24% and 51.72%) of undergraduate and graduate student/endodontists respectively showed interest in using the pictograph method in their professional career. Conclusion: the pictograph method in endodontic diagnosis is accepted by the majority of undergraduate and graduate students/endodontists. Training and experience affect the diagnosis making. KEYWORDS Advanced dental education; Continuing dental education; Endodontics; Pictograph